Evaluation of Antibacterial Activity of Cinnamomum Zeylanicum Extract on Cariogenic Microorganisms of the Dental Plaque In-Vitro Study and Scanning Electron Microscopic Assessment (Mustansiria Dental Journal, 2018)
The present study was conducted to evaluate the antibacterial activity of Cinnamomum zeylanicum aqueous extracts and ethanol extracts on different type of dental plaque microorganisms. Screening study was performed to detect the potential antibacterial activity against S. aureus, E. coli, S. mutans, Lactobacillus and dental plaque pool samples. From the screening test, Minimum Inhibitory Concentration (MIC) values were determined. The lowest MIC value was 25 mg/ml of aqueous and 12.5 mg/ml of ethanol extract for S. aureus. The highest MIC values were seen in dental plaque anaerobic pool samples with 300 mg/ml of aqueous extract and 150 mg/ml of ethanol extract. The MIC values for aqueous extracts ranged from 25 to 300 mg/ml where as ethanol extract ranged from 12.5 to 150 mg/ml. The high concentration of ethanol extract, 100 mg/ml in the fixed plant concentration test showed the most inhibition effect for all the organisms tested. Generally, the Cinnamomum zeylanicum ethanol extracts demonstrated a stronger antibacterial activity compared to the aqueous extract. This study also compares the antibacterial activity of chlorhexidine with the plant extracts but chlorhexidine showed a higher antibacterial effect on the microorganisms where almost all organisms inhibited The morphological structures of S. mutans Lactobacillus were observed under SEM before and after treatment with Cinnamomum zeylanicum extracts and chlorhexidine digluconate mouthwash. This study did not detect any physical changes occurring in shapes and structures of the bacteria after treatment with Cinnamomum zeylanicum extracts. The scanning electron micrograph of bacteria after treatment with chlorhexidine digluconate mouthwash showed visible changes in the shapes and structures of the bacteria. Cinnamomum zeylanicum present promising antibacterial properties which could be used to inhibit dental plaque formation